Analisis Multi Kriteria Sebagai Metode Pemilihan Suatu Alternatif Ruas Jalan di Propropinsi Lampungampung - Rahayu Sulistyorini (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2010)
Multi-Criteria Analysis (MCA) is a decision-making tool developed for decision-making process, using several criterias and select the best alternative based on those criteria. This method use perception of stakeholder on variables which is compared in decision making process. The aim of MCA is to find selected route using several alternatives which is give contribution for development area, accessibility, eficien and minimise environment impact and social aspect. Some criteria which is used in this analysis are accessibility , environment impact, area development, road system improvement, social aspect, construction cost and safety. The result of interview is used to determine the weightening of criteria. The methodology to achieve the goal is built pairwise comparison matrix and calclate the average of the result. From the analysis we can resume that the important variable is environment preservation. The best route of this alternatives is first route: simpang Kalinangkal-Tanjung Balok through Sungai langka-Bogorejo-Karangsari-Sukadadi.